Oral Health-Related Quality of Life in the Elderly Population Receiving Health Care at the Public Hospital Network in Medellín, Colombia, and its Related Factors (2016)
ABSTRACT: Metrosalud is the largest public hospital network in the city of Medellin and one of the most important in Colombia providing health care to the most vulnerable population. The objective of the study was to determine the Oral HealthRelated Quality of Life (OHRQoL) and its related factors in the elderly population receiving health care at the public hospital network in Medellin (Colombia). A crosssectional design was used. Men and women ≥ 65 years old were considered for this research, selected from first consultation records by the institution’s statistical unit for 2011, who accepted to participate after being contacted by telephone. Sampling was performed in two stages: simple random sampling for selecting Hospital Units HU and Health Centers HC throughout the hospital network in the city, followed by random quota sampling in proportion to the number of elderly population assigned to each HU and HC. A total 342 patients (58.2% women) participated in the study. The project involved the use of a structured questionnaire and complete dental examination with information on sociodemographic data, selfperceived health variables (mental, general and oral), use of oral health services, Oral HealthRelated Quality of Life (OHRQoL as measured with GOHAI index), temporomandibular joint test, oral mucosa, soft tissue evaluation, periodontal, dental and prosthetic examination. Descriptive and bivariate analyses were conducted to determine statistically significant differences. Multivariate analysis was performed, using logistic regression, calculating crude and adjusted odds ratios (OR) with their 95% confidence intervals (95% CI). Impacts were found to be generated by education levels, differences in socioeconomic status and urban or rural housing conditions. The results of this research show low OHRQoL levels in the elderly population receiving health care services at the public hospital network in Medellin.